Perceived importance of pandemic interventions for attending cultural events: findings from Germany - Weber, Michaela; Plew, Manuel; Neumann, Christine; Ostendorf, Marietta; Herr, Raphael; Fischer, Joachim E. (BMC public health, 2022)
During the first waves of the COVID-19 pandemic, many cultural and sporting events were held without spectators or had to be cancelled. Therefore, several containment strategies to provide requirements for safe events were developed and tested. Nonetheless, every second (50.7%) is afraid of becoming infected on an event. We therefore investigated which hygiene and containment measures are perceived to be important from the visitor’s point of view and thus might increase subjective sense of safety. This online study was carried out in November 2020. A total of 1,004 persons, who regularly attended events before the pandemic, took part in the study. The importance of different hygiene and containment measures was evaluated using a 5-point Likert-scale (1 “unimportant” to 5 “extremely important”). Potential statistical differences in socio-demographical aspects (age, gender, net disposable income for leisure activities) and attendance on events were tested with analyses of variance. Participants perceived the use of disinfectant (M = 4.10) as the most important element of containment strategies, followed by transparent information on the hygiene strategy (M = 4.00), reduced occupancy (M = 3.98), and optimized ventilation (M = 3.97). Body temperature measurement at the entrance (M = 3.27), a negative SARS-CoV-2 test (M = 3.11), completion of a health questionnaire (M = 3.05), and abandoning breaks and catering (M = 2.98) were considered as less important. Analyses of group differences in socio-demographical aspects found abandoning breaks and catering to be more important to men than to women. This strategy is also more important to people aged 66 and above than to younger age groups (e.g., age 20-40). For women, the use of disinfectant is considerably more important. No other significant differences exist. Combining relevant measures appears to be important to provide a safe containment strategy. Measures aimed at positively influencing people’s sense of safety do not fully correspond to researched knowledge of effectiveness. There are also target group-specific differences in the rating of measures, which should be considered while preparing containment strategies. To describe the dynamic development of changes in subjective rating of containment strategies, continuing research is needed.
Gesehen am 11.03.2024